Motor Impulsivity and Learning of BasketballBasic Skills - Mohamad Hosein Ghahramani; Mahdi Sohrabi; Alireza Saberi Kakhaki; Mohammad Ali Besharat (University of Tehran, 2016)
Impulsivity features of individuals affect their movement patterns when learning sports skills. Therefore, this study examined the effect of different levels of motor impulsivity on learning basketball basic skills. 3 groups of boys aged between 10 and 12 who were selected according to motor impulsivity levels participated in a basketball skills training course along with a control group (the subjects were randomly selected). To evaluate their performance,AAHPERD and Hann basketball pass tests were used in thepretest, posttest, retentionandtransfer phases. The results of covariance and analysis of variance in posttest (P=0.0001) andretention test (P=0.011) inAAHPERD basketball pass showed a significant advantagein this test along with increased motor impulsivity levels.However,better performance were along with decreased impulsivity levelsinHann pass task. The observed differences among the groups were not statistically significantin the transfer phase(P=0.112). It can be concluded that different levels of motor impulsivity is one of the main factors affecting sport skills learningwith regard to the speed-oriented and accuracy-oriented skills.